Open Source Web Platform for the Analysis of Academic Spin-offs - Fernando Almeida; Eugénio Cunha (Journal of Information Systems Engineering and Business Intelligence, 2018)
Universities have assumed an increasingly important role in transferring technology to society with a strong economic impact. The companies originated from the academic environment, called academic spin-offs, have fostered the appearance of new projects based on emerging technologies and knowledge, created by young students and researchers who seek to launch their own business and generate new jobs in society. However, the number of existing studies on academic spin-offs is limited and restricted to the specific national realities, and the results of these studies are typically incorporated only in scientific manuscripts. In this sense, this study proposes a web platform that allows the analysis of academic spin-offs according to multiple dimensions, such as firm, institutions, individual, localization, science parks, financial data and corporate actions. The application is built exclusively in open source technologies and allows data to be explored in real-time and interactively. The results obtained allow us to evaluate the behavior of the application regarding fundamental elements in the success of the adoption of a Web application, such as usability, security, interoperability and portability.